Mental health tracking among young Russians: practices and motivations - Alexandra Paramonova; Oxana Mikhaylova (Discover Mental Health)
Abstract The rapid development of digital mental health services can be attributed to the confluence of factors such as the rise of digitalization, individuals’ increasing agency within medical systems across the globe, and the broader trend of fostering neoliberal subjects who assume responsibility for their own health. However, the relationship between agency in addressing mental health issues and adhering to the conventional paradigm of medicalized cognition remains unclear. In this paper, we investigate the practices and motivations of young Russians using mental health apps through the conceptual frameworks of Foucault and Giddens. Our sample consisted of 22 in-depth interviews with Russians aged between 18 and 29. Findings suggest that mental health narratives are highly individualized and correspond with a neoliberal conceptualization of agency. Trackers serve as tools of self-reflection that eschew intentions to change oneself due to their reliance on manual data input, which undermines Foucault’s analysis of self-tracking.